(untitled) (Research, Society and Development, 2023)
Teaching today is moving through new realities. The teaching-learning process needs the knowledge reconstructed by the student. Active methodologies and information and communication technologies bring benefits and overcome the traditional model. The objective of this study was to analyze the application of a pedagogical intervention for the teaching-learning process and the opinion of students enrolled in the child health course of the nursing major at a private community university. It is an applied study, quantitative approach, exploratory design, through experimental technical procedures and action research. Resolution 466/12 of the National Health Council was respected. The collection occurred with the application of the instruments using the tools Socrative and Google Forms. For analysis, the Kruskal Walis Test Average Ranking calculation was used. The study included 33 students enrolled in the 6th semester. There was a predominance of 9 (27.2%) students aged between 21 and 25 years and 14 (42.5%) who work as nursing technicians. All participants have internet access at home. The percentage of correct answers at Peer Instruction averaged 71.9%. As for the opinion, there was a greater agreement and acceptance by the subjects. It was considered that the conflict of generations is present and that the greatest agreement and acceptance about the pedagogical intervention goes against the trajectory of teaching today. The future, new generations, and technology reserve a new perspective on education. Further research on this topic is suggested to promote qualified training for health professionals.